Measurement of Gene Regulation in Individual Cells Reveals Rapid Switching Between Promoter States - Sepúlveda, Leonardo A. (Science, 2016)
In vivo mapping of transcription-factor binding to the transcriptional output of the regulated gene is hindered by probabilistic promoter occupancy, the presence of multiple gene copies, and cell-to-cell variability. We demonstrate how to overcome these obstacles in the lysogeny maintenance promoter of bacteriophage lambda, P(RM). We simultaneously measured the concentration of the lambda repressor CI and the number of mRNAs from P(RM) in individual E. coli cells, and used a theoretical model to identify the stochastic activity corresponding to different CI binding configurations. We found that switching between promoter configurations is faster than mRNA lifetime, and that individual gene copies within the same cell act independently. The simultaneous quantification of transcription factor and promoter activity, followed by stochastic theoretical analysis, provides a tool that can be applied to other genetic circuits.